Up-scaled solid state reaction for synthesis of doped Mg2Si. (February 2017) - Kim, Gwansik; Lee, Hwijong; Kim, Jeongmin; Roh, Jong Wook; Lyo, Inwoong; Kim, Byung-Wook; Lee, Kyu Hyoung; Lee, Wooyoung
Abstract: Herein, we reported a synthesis technique based on the up-scaled solid state reaction for Al and Bi co-doped Mg2 Si polycrystalline bulks and investigated their thermoelectric transport properties. The powders ( 1 kg/batch) were synthesized for mass production by using the solid state reaction, and the polycrystalline bulks were consolidated with a diameter of 25 mm and thickness of 3 mm using hot pressing and spark plasma sintering techniques. Both the hot pressed and the spark plasma sintered bulks showed good reproducibility and positional uniformity of the thermoelectric properties and the highest ZT value of 0.98 was obtained at 873 K. Graphical abstract: